Health-Saving Competence of Teachers is an Important Indicator of Their Professional Activities - S. T. Tursunov (Researchparks Publishing, 2022)
The article deals with the issues of developing the health-saving competence of teachers, which contributes to improving the quality of education, preserving and strengthening the health of students and considered as an important indicator of the professional activity of teachers.